1997
DOI: 10.1002/eji.1830271137
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between membrane IgM and the cytoskeleton involve the cytoplasmic domain of the immunoglobulin receptor

Abstract: Cross-linking induced interactions between the membrane form of immunoglobulin (mIg) and the cytoskeletal matrix have been described by several groups. To date, the function of mIgM association with the cytoskeleton is not yet understood. Delineation of the molecular basis of these interactions will be instrumental in elucidating their function. We have previously shown that the Ig alpha/beta heterodimer is not required for ligand-induced mIgM binding to the cytoskeleton. In this study, we have investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Colocalization of BCRcontaining vesicles with the actin cytoskeleton may not necessarily indicate a direct interaction between the BCR and actin filaments. However, the data from this and previous studies are consistent with an interaction between the BCR and the actin cytoskeleton that is up-regulated by BCR activation (21)(22)(23)(24). This interaction may be either direct or indirect through adaptor proteins and actin-binding proteins recruited by the activated BCR (48,49).…”
supporting
confidence: 87%
“…Colocalization of BCRcontaining vesicles with the actin cytoskeleton may not necessarily indicate a direct interaction between the BCR and actin filaments. However, the data from this and previous studies are consistent with an interaction between the BCR and the actin cytoskeleton that is up-regulated by BCR activation (21)(22)(23)(24). This interaction may be either direct or indirect through adaptor proteins and actin-binding proteins recruited by the activated BCR (48,49).…”
supporting
confidence: 87%
“…A stimulation-dependent and -independent association of cytoskeletal components with both B-and T-cell antigen receptors has been reported previously (4,20,24,31). Antigen-mediated reorganization of the microtubule-organizing center in T cells and the F-actin assembly in B cells is ITAM dependent (6,19).…”
Section: Discussionmentioning
confidence: 66%
“…The initial studies in 1970 reported a redistribution of the actin motor protein myosin from the cell periphery to the BCR central cluster in response to BCR cross-linking by antibody [47] and an accumulation of the actin cytoskeleton at the plasma membrane of B cells in response to mitogens [48,49]. BCR cross-linking was later found to cause the association of surface BCRs and proximal signaling components with detergent insoluble cytoskeletal fraction of cells [50-53]. These implicate a physical and functional relationship of actin with surface BCRs and BCR signaling complexes.…”
Section: Actin Reorganization During Bcr Activationmentioning
confidence: 99%
“…An early observation that antigenic activation influences the physical relationship of both BCR and signaling molecules with the cytoskeleton [50-53] suggests another mechanism for actin to facilitate signaling: the actin cytoskeleton with actin adaptor proteins potentially serves as a scaffold to recruit and position signaling molecules physically close to the BCR. The reassembly of the actin cytoskeleton and the re-association of active ezrin with the lipid raft-associated-Csk binding protein after the initial detachment and disassembly can compartmentalize membrane proteins for receptor clustering and receptor signaling complex formation.…”
Section: Roles Of the Actin Cytoskeleton In Bcr Signalingmentioning
confidence: 99%